Pengaruh Service Excellent Petugas Check In Counter Terhadap Kepuasan Pelanggan Maskapai Penerbangan Lion Air di Yogyakarta International Airport - Geraldia Aurelia Nira; Maria Valeria Roellyanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This research was written to find out the Effect of Service Excellent Check-In Counter Officers on Lion Air Passenger Satisfaction at Yogyakaeta International Airport. This research was written to find out how much influence service excellent has on customer satisfaction at Lion Air at the Yogyakarta International Airport. Excellent service in the service sector is taken into account, because the excellent service of the check-in counter staff has an impact on the satisfaction felt by customers. The results of this study can be used as input in order to improve service excellence on the performance of check-in counter officers for Lion Air so that it can reflect the quality of the products produced, especially for guaranteeing customer satisfaction. This study used a quantitative method, with data collection techniques using a questionnaire in which the questionnaire was distributed to passengers who had used Lion air flight services at the Yogyakarta International airport. Respondents in this study were 100 respondents. and data selected using probability sampling or (simple random sampling) the results of data collection will be processed using SPSS to obtain results. The results of this study indicate that there is a significant influence between service excellent on Lion air airline customer satisfaction at Yogyakarta International airport. The t test was carried out which produced t count (9.622) greater than t table (1.660) and R square or a coefficient of determination of 48.6%, so that H0 was rejected and Ha was accepted. This means that there is an influence of excellent service on customer satisfaction.